ACTION AGAINST THE ENVIRONMENT IN THE HIGH VILLAGES, THE DREAD OF THE ANCIENT WILDERNESS, THE CAPTIVITY OF THE TOBA - Nasution, Lita; Ranita, Sylvia Vianty; Barus, Wan Arfiani; Sinulingga, Lismayarti; Manurung, Rista (Journal of Community Research and Service, 2024)
In Hatinggian Village, precisely in Lumban Julu District, Toba District, there is an action to care for the environment that is worthy of respect. The local communities in the village have made extraordinary efforts to preserve and sustain the surrounding environment. Through the implementation of the community self-serving activities of the Muhammadiyah University of North Sumatra in the village of Hatinggian, Lumban Julu district, Toba District, North Sumatera Province, which was carried out from August 25 to September 3, 2022, through interviews and field observations, it can be concluded that the activities are running well and smoothly. Through this community service activity, students participating in community service have the opportunity to implement the knowledge acquired during the lecture, then gain valuable insights and experiences from the community, such as training themselves to be responsible, having a sense of sympathy and empathy, and learning independently to find innovations and solutions to solving an existing problem.